Market access and the evolution of within plant productivity in Chile - Maria Bas; Ivan Ledezma (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper studies the impact of trade reforms on the evolution of plant's productivity in Chile (1979-2000). The main contribution of the paper is to construct detailed measures of trade liberalization disentangling the impact of export and import oriented policies. We find evidence of a positive impact of export oriented policies on productivity of traded sectors relative to non traded. On the other hand, the reduction of import barriers might have a positive impact on productivity in export oriented sectors, but it hurts local firms in import competing ones probably due to the existence of increasing returns.
Keywords: F10; F12; F41; 330; Außenhandelsliberalisierung; Produktivität; Exportindustrie; Importsubstitution; Handelbares Gut; Nicht-handelbares Gut; Chile